FINITE ELEMENT ANALYSIS OF ANTENNA-FEEDER SYSTEM ON TRUCKBORNE RADARS - HUANG QiongQiong (Jixie qiangdu)
A truckborne radar system is widely applied in communication,radar navigation and electronic countermeasures,etc,and it can work in an extremely harsh field environments. The antenna-feeder system of a truckborne radar,due to its working characteristics,the wind load is its main load,analysising its wind loads has an great significance to guarantee structural strength and stiffness. This article using finite element method for the radar antenna-feeder system of mechanical characteristics of static and transient under wind loads,analysis its structure’s characteristics of displacement,stress and strain under static and dynamic loads change over time by using transient dynamic,and giving the analysis of the moire fringe,providing basis of optimal design of antenna-feeder system.